TAX MANAGEMENT: Tax Compliance and Regulation in ASEAN Countries - Sumarno Manrejo; Gilbert Rely; Endah Prawesti; Achmad Fauzi; Alifia Amalia (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study is a comparative study of tax treatment policies in ASEAN countries in an effort to improve tax compliance. Tax compliance is very important for the country because it will have a direct impact on increasing state revenues in an effort to ensure the smoothness of public spending. In addition, tax compliance is one indicator of public trust in the government in the taxation system implemented . Tax compliance in ASEAN shows significant variations between countries. In general, the tax ratio in Asia Pacific ranges from 7.8% to 18.7%, there is a very diverse gap between countries. The factors that influence compliance tax includes taxpayer income, tax rates, non-taxable income, government administration, commitments as well as coordination between related state institutions tax , level similarity perception about tax between must tax and fiscus , role owner business in collect , deposit as well as report tax . ASEAN countries can always implement all policies in terms of tax collection for corporations and individuals in supporting sustainable development policies, building community welfare and avoiding double taxation. This study aims to compare the treatment of tax policies in ASEAN countries and at the same time provide strategic recommendations in tax management efforts in an effort to increase tax compliance.